2009
DOI: 10.1007/s00011-009-0087-6
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of ongoing experimental autoimmune myasthenia gravis by transfer of RelB-silenced bone marrow dentritic cells is associated with a change from a T helper Th17/Th1 to a Th2 and FoxP3+ regulatory T-cell profile

Abstract: RelB-silenced DCs were able to create a particular cytokine environment that was absent of inflammatory cytokines. RelB-silenced DCs provide a practical means to normalize the differentiation of the four T-cell subsets (Th17, Th1, Th2, and Treg) in vivo, and thus possess therapeutic potential in Th1/Th17-dominant autoimmune disorders such as myasthenia gravis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 54 publications
(57 reference statements)
0
34
0
Order By: Relevance
“…Also, the proliferative response of T cells in response to AChR stimulation was increased when stimulated by IL-17 in vitro [64e66]. Moreover, treatment with immunosuppressive bone marrow stromal cells or dendritic cells ameliorated EAMG symptoms by shifting the balance from Th1/Th17 dominance towards Th2/Treg dominance [65,66]. A similar balance between regulatory and inflammatory T cells was also observed in a clinical study, in which MG patients with reduced Treg cells showed more severe MG symptoms [67].…”
Section: Th1/th17 Versus Th2-type Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the proliferative response of T cells in response to AChR stimulation was increased when stimulated by IL-17 in vitro [64e66]. Moreover, treatment with immunosuppressive bone marrow stromal cells or dendritic cells ameliorated EAMG symptoms by shifting the balance from Th1/Th17 dominance towards Th2/Treg dominance [65,66]. A similar balance between regulatory and inflammatory T cells was also observed in a clinical study, in which MG patients with reduced Treg cells showed more severe MG symptoms [67].…”
Section: Th1/th17 Versus Th2-type Immunitymentioning
confidence: 99%
“…Intravenous injection of RelB-silenced dendritic cells to B6 mice with established EAMG effectively reduced muscle weakness. This effect was associated with a shift from Th1/Th17 to a Th2 and regulatory T cell profile [65]. Moreover, administration of granulocyteemacrophage colony stimulating factor (GM-CSF), a growth factor promoting anti-inflammatory dendritic cell production, before or after EAMG induction resulted in decreased EAMG incidence and severity in B6 mice [71].…”
Section: Dendritic Cell Manipulation As a Treatment Modelmentioning
confidence: 99%
“…All of these proteins have been knocked out in mice, and deficiency of RelB or a combined deficiency of RelA and p50 or c-Rel and p50 all result in DC loss (22,23). The noncanonical transcription factor RelB has further been shown to have a critical role in DC maturation and immunogenicity (22,(24)(25)(26)(27). Canonical NF-kB activation, which involves phosphorylation and subsequent degradation of the inhibitory IkB proteins enabling nuclear translocation of RelA, c-Rel, and/or p50 dimers, has also been associated with activationinduced DC maturation and function (28)(29)(30)(31).…”
mentioning
confidence: 99%
“…The efficacy of this treatment is due to the activation of specific DC subpopulations and expansion of the regulatory T-cell compartment (Sheng et al 2006). Finally, recent data demonstrate that the administration of bone marrow DC, RelB-silenced and pulsed with Ta146-162, is able to suppress EAMG progression in mice, by inducing a positive shift in favour of Th2/regulatory T cell responses (Yang et al 2010).…”
Section: Induction Of Peripheral Tolerancementioning
confidence: 99%